2013
DOI: 10.3724/sp.j.1006.2012.00275
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping for Anthocyanin and Melanin Contents in Maize Kernel

Abstract: Anthocyanin and melanin are important and beneficial chemical components in black maize kernel. It is important to comprehensively study the QTL mapping for anthocyanin and melanin, cloning and transfer of pigmentation-related genes and marker assistant breeding. In this study, two related F 2:3 populations derived from crosses of Mu6×SDM (WD) and Mo17×SDM (YD) were used to identify QTLs for anthocyanin and melanin contents in maize kernels. The results showed that the phenotype and QTL identification of two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the MoS‐BC 4 F 3 population, two QTLs for kernel anthocyanin content and cob anthocyanin content were mapped in the interval S8 to mmc0523 on chromosome 6 and in the interval bnlg1028 to IDP8526 on chromosome 10, respectively. Compared with the study of Qin et al, (2012), the intervals of the QTLs in this paper were all narrowed. In both populations, there were two common markers ( S8 on chromosome 6 and IDP8526 on chromosome 10), which illustrated that the two QTLs were reliable.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the MoS‐BC 4 F 3 population, two QTLs for kernel anthocyanin content and cob anthocyanin content were mapped in the interval S8 to mmc0523 on chromosome 6 and in the interval bnlg1028 to IDP8526 on chromosome 10, respectively. Compared with the study of Qin et al, (2012), the intervals of the QTLs in this paper were all narrowed. In both populations, there were two common markers ( S8 on chromosome 6 and IDP8526 on chromosome 10), which illustrated that the two QTLs were reliable.…”
Section: Discussionmentioning
confidence: 56%
“…Until now, numerous studies on black maize have been done. Qin et al (2012) identified the QTLs for anthocyanin and melanin contents in maize kernels. Mei et al (2014) analyzed the physicochemical characteristics of anthocyanin in SDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated obvious QTL enriched regions and clustered distribution of avonoidrelated traits in the chromosomes of sweet corn. Similar studies are available on the clustering distribution of QTLs (Qin et al 2012;Luo et al 2019). Tuberosa et al (2002) reported that QTL mapping analysis provides insights into trait correlations and suggested four mechanisms: (1) close linkage of genes controlling distinct traits at identical or adjacent chromosomal loci; (2) mono-functional genes orchestrating cascades of genes; (3) pleiotropic gene effects; and (4) two tightly linked genes jointly modulating multiple distinct traits.…”
Section: Accuracy Of Qtl Mapping In Il and Ril Populationsmentioning
confidence: 84%
“…The results further con rmed the important role of p site in the avonoid metabolic pathway in maize and the reliability of the experimental results. The QTLs (qAPI4.2a and qNAR4.3c) located in the region of chromosome bin4.06-bin4.07 were located at adjacent loci with QTL (qFCK-4-HN) controlling total avonoids(Sun et al 2013) and QTL (qACK-4a) controlling anthocyanins(Qin et al 2012). The QTL (qAPI5a) located at the bin5.03 locus of chromosome was located at the same locus as the QTL controlling maysin(Meyer et al 2007).…”
mentioning
confidence: 99%